The Eveningness Chronotype and Lower Adherence to the Mediterranean Diet Are Associated With Depressive Symptoms in Older Subjects With Metabolic Syndrome. (7th June 2021) - Coltell, Oscar; Alvarez-Sala, Andrea; Gimenez-Alba, Ignacio; de la Camara, Edurne; Fernández-Carrión, Rebeca; Sorlí, José; Corella, Dolores
Abstract: Objectives: Studies have shown the importance of depression as a risk factor for several diseases. Likewise, currently there is great interest on the role of chronotype in depressive disorders. Similarly, associations between diet and depression have been reported. However, very few studies have analyzed the combined effect of diet and chronotype on depression. Our aim was to investigated the joint influence of the morning/evening chronotype and adherence to the Mediterranean diet (MeDiet) on depressive symptoms in older subjects with metabolic syndrome. Methods: We analyzed 465 PREDIMED Plus-Valencia study participants (aged 55–75). We assessed depressive symptoms by the Beck Depression Inventory (BDI). A higher score indicated more severe depressive symptoms. Adherence to the MedDiet was evaluated by the 17-item MeDiet score. Chronotype was assessed with the Morningness-Eveningness Questionnaire (MEQ). A higher total score indicated morningness. The 5 MEQ cut-offs were: definitely morning type, moderately morning type, intermediate type, moderately evening type, and definitely evening type. Multivariable models with interaction terms were fitted. Results: Depressive symptons were statistically higher in women ( P  = 1.5 × 10–8) and in type 2 diabetes participants ( P  < 0.01). Adherence to the MeDiet was inversely associated with depression in the whole population ( P  < 0.001) and no significant heterogeneity by sex or by diabetes status was detected (P-interactions < 0.05). The morningness-eveningness mean score was inversely associated with depression, being the association statistically higher when we used the 5-categories for chronotypes. In a multivariable regression model adjusted for sex, diabetes, age, body mass index and physical activity, both adherence to the MedDiet (beta = –0.28; P  = 0.010) and the chronotype (beta = –0.90; P  = 0.047) remained statistically associated with the BDI score, showing additive effects. When we tested the interaction terms between chronotype and MedDiet adherence ( P  = 0.498) no significant heterogeneity was found. Conclusions: The eveningness chronotype was associated with higher depressive symptoms, but a higher adherence to the MeDiet (inversely related with depression) may counteract the chronotype risk in an additive effect. Funding Sources: CIBEROBN 06/03/035, PROMETEO 17/2017, P1 1B201354.